Reconfigurable ultra wideband (UWB) antenna design and development - Abd Rahman, Tharek; Ngah, Razali; Rahayu, Yusnita; Ahmad, Mohd. Riduan; Abu, Mohammed Khomeini (Faculty of Electrical Engineering, 2008)
A few years after the early investigation on ultra wideband (UWB) wireless system, considerable research efforts have been put into the design of UWB antennas and systems for communications. These UWB antennas are essential for providing wireless wideband communications based on the use of very narrow pulses on the order of nanoseconds, covering a very wide bandwidth in the frequency domain, and over very short distances at very low power densities. In this project, new models of T, L and U slotted UWB antennas are proposed by studying their current distribution characteristics. The wideband behavior is due to the fact that the currents along the edges of the slots introduce an additional resonance, which, in conjunction with the resonance of the main patch, produce an overall broadband frequency response characteristic. These antennas are considerable small than others listed in the references, which their sizes are less than a wavelength, compact, and suitable for many UWB applications. The configuration of slots type for both patches and feeding strip are considered as a novelty and contribution in this project. The geometry of the antenna implies the current courses and makes it possible to identify active and neutral zones in the antenna, thus it will be possible to fix which elements will act on each characteristic. This project also investigated the ability of slotted UWB antennas to reject the interference from licensed Fix Wireless Access (FWA), High performance local area network (HIPERLAN) and wireless local area network (WLAN) within the same propagation environment. Inserting a half-wavelength slot structure with additional small patches gap attached have resulted frequency notched band characteristics. The small patches gap instead of switching. The measured return loss, radiation patterns, and phase agree well with the simulated results. The antenna provides an omnidirectional pattern with the return loss less than -10 dB and linear in phase.